3/5x + 22 = 28
-22. -22
3/5x = 6
(5/3)(3/5)x = 6 × (5/3) multiply by the reciprocal
x = 6 × (5/3) -------------> 6 and 3 can be simplify so it will be x = 2 × 5 = 10
check
3/5 (10) + 22 ---> 3 × 2 + 22
28 = 28 ✔
Step-by-step explanation:
18/24>20/24 you have to flip the sign to make it correct
Answer:
The roots of the given equation is x=4,3i,-3i
Step-by-step explanation:
The given cubic equation is
![y=x^3-4x^2+9x-36](https://tex.z-dn.net/?f=y%3Dx%5E3-4x%5E2%2B9x-36)
To find the roots we have to equate the equation to zero
ie, ![x^3-4x^2+9x-36=0](https://tex.z-dn.net/?f=x%5E3-4x%5E2%2B9x-36%3D0)
It can be done by using Synthetic division method
Therfore [tex](x-1) is not a factor or root
now put x=-1
Therfore [tex](x-1) is not a factor or root
similarly let x=2,-2,3,-3 all not equal to zero so the are not roots.
let x-4 is a factor of given equation
then it satifies the equation ie (x-4) is a root
And it may be written as
[tex](x-4)(x^2+9)